Multimodality Treatment of Bile Duct Stone - Arief Hakiki; Marcellus Simadibrata; Agi Satria Putranto; Nur Rasyid (The Indonesian Society for Digestive Endoscopy, 2009)
Gallstone and bile duct stone is a common disease and affects people from every society, race, age and gender. Advance in medicine has led us to a new paradigm of bile duct stone treatment. Endoscopic procedures for bile duct stone by means of Endoscopy Retrograde Cholangio-pancreatography (ERCP), sphincterotomy, balloon dilation, basket extraction, and lithotripsy, and even using laser as well as the shockwave-has brought a lot of novel innovation with high success rate. Appropriate indication and the ability to recognize various risk factors of complication are the keys to successful treatment, in order to decrease morbidity and mortality rate. Multimodality treatment of bile duct stone includes endoscopy, surgery, and drugs are a treatment approach which has always to be carried out in bile duct stone management. Difficult bile duct stone cases such as large stone, impacted stone, biliary stone in pregnancy, and recurrent stone can be treated by endoscopy with excellent success rate particularly if it is accomplished using multimodality treatment. Keywords: bile duct stone, endoscopy, ERCP, sphincterotomy, mechanical lithotripsy, laser lithotripsy, shockwave, cholecystectomy laparoscopy, precut sphincerotomy